Advanced Abdominal Pregnancy: A Case Report - Hamid, Ayinur Nahar; Begum, Rokeya; Sultana, Zakeya; Akhter, Nargis (Journal of Chittagong Medical College Teachers’ Association, 2011)
DOI: 10.3329/jcmcta.v21i1.7684 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):74-76